The Index of Microcirculatory Resistance Postpercutaneous Coronary Intervention Predicts Left Ventricular Recovery in Patients With Thrombolyzed ST‐Segment Elevation Myocardial Infarction. (29th January 2016) - Palmer, Sonny; Layland, Jamie; Carrick, David; Williams, Paul D.; Judkins, Christopher; Gong, Fei Fei; Burns, Andrew T.; Whitbourn, Robert J.; MacIsaac, Andrew I.; Wilson, Andrew M.
Abstract : Background: The index of microcirculatory resistance (IMR), an invasive measure of microvascular function, has been shown to correlate with clinical outcomes in patients with ST‐segment elevation myocardial infarction (STEMI). The aim of this study is to evaluate the predictive value of IMR on left ventricular recovery in patients undergoing a pharmacoinvasive strategy for STEMI. Methods: The index of microcirculatory resistance was assessed following percutaneous coronary intervention (PCI) in 31 patients with STEMI who were initially managed with thrombolysis. Other markers of microvascular function such as coronary flow reserve (CFR), TIMI flow grade, corrected TIMI frame count (cTFC), and ST‐segment resolution were also recorded. All indices were evaluated against measures of left ventricular function and recovery 3 months postindex event. Results: The IMR correlated with left ventricular function, as assessed by wall motion score and ejection fraction at 3‐month follow‐up (r = 0.652, P = 0.005; r = −0.452, P = 0.011, respectively). The traditional methods of assessing microvascular function, such as CFR, TIMI flow grade, cTFC, and ST‐segment resolution did not correlate with wall motion score and ejection fraction at 3 months. Post‐PCI IMR was significantly lower in those patients with left ventricular recovery at 3 months (18 U vs 39 U, P < 0.001). The optimal cut‐off value for post‐PCI IMR and left ventricular recovery was 32 U. In patients in whom the IMR was greater than 32 U, the percent change in ejection fraction was significantly lower than in those patients in whom the IMR was less than 32 U (2 ± 11 vs 12 ± 8, P = 0.012). Conclusions: In patients presenting with STEMI initially managed with thrombolysis and subsequently undergoing PCI, IMR correlates with measures of left ventricular function and has the potential to predict left ventricular recovery at 3 months. (J Interven Cardiol 2016;29:146–154)